Evidence for risk of bias in cluster randomised trials: review of recent trials published in three general medical journals. Issue 7418 (2nd October 2003) - Puffer, Suezann; Torgerson, David; Watson, Judith
Abstract: Objective To examine the prevalence of a risk of bias associated with the design and conduct of cluster randomised controlled trials among a sample of recently published studies. Design Retrospective review of cluster randomised trials published in the BMJ, Lancet, and New England Journal of Medicine from January 1997 to October 2002. Main outcome measures Prevalence of secure randomisation of clusters, identification of participants before randomisation (to avoid foreknowledge of allocation), differential recruitment between treatment arms, differential application of inclusion and exclusion criteria, and differential attrition. Results Of the 36 trials identified, 24 were published in the BMJ, 11 in the Lancet, and a single trial in the New England Journal of Medicine . At the cluster level, 15 (42%) trials provided evidence for secure allocation and 25 (69%) used stratified allocation. Few trials showed evidence of imbalance at the cluster level. However, some evidence of susceptibility to risk of bias at the individual level existed in 14 (39%) studies. Conclusions Some recently published cluster randomised trials may not have taken adequate precautions to guard against threats to the internal validity of their design.